Adobe After Effects CC : 2018 release - Gyncild, Brie, ....-; Fridsma, Lisa, ....- ([San Francisco] : Adobe Press, 2018)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe After Effects CC (2018 release) choose Adobe After Effects CC Classroom in a Book (2018 release) from Adobe Press. The 15 project-based lessons in this book show users step-by-step the key techniques for working in After Effects. Learn how to create, manipulate, and optimize motion graphics for film, video, DVD, the web, and mobile devices. Gain hands-on experience animating text and images, customizing a wide range of effects, tracking and syncing content, rotoscoping, and correcting color. Create Motion Graphics templates in After Effects so colleagues can make specific edits in Premiere Pro without accidentally changing other critical settings. Learn to create 3D content with both After Effects and Maxon Cinema 4D Lite (included with the software). The online companion files include all the necessary assets for readers to complete the projects featured in each chapter as well as ebook updates when Adobe releases relevant new features for Creative Cloud customers. All buyers of the book get full access to the Web Edition: a Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.